Investigation Non-economics Factors to The Tax Compliance of Village Treasurer in Kulon Progo District - Piastini Gunaasih, Sang Ayu Putu; Ningsih, Maria Pipit Setia (Accounting Analysis Journal, 2024)
Purpose: This study investigated the influence of religiosity, mastery of information technology, and understanding of tax knowledge on the compliance of taxpayers in Kulon Progo district, DIY. Taxpayer compliance was about reporting and withholding when reporting taxes. Method: Three hypotheses were developed and then tested using the multiple linear regression method. The method used for data collection is the survey method. Questionnaires were distributed online using the Google Form application to 87 village treasurer taxpayer spread across 87 villages in the Kulon Progo district. Findings: The data obtained is then validated and checked for reliability. The results showed that religiosity and understanding of tax knowledge have a positive effect. In contrast, mastery of technology does not affect of village treasurer taxpayer compliance. Novelty: This study contributes in several ways. First, tax compliance in village treasurers is still very rare. Second, it is hoped that the empirical evidence from this research can provide input or consideration for regulators and tax authorities regarding how the technology can be more effective and efficient.